A simple non-recessed and Au-free high quality Ohmic contacts on AlGaN/GaN: The case of Ti/Al alloy. (May 2018) - El-zammar, Georgio; Yvon, Arnaud; Khalfaoui, Wahid; Nafouti, Maher; Cayrel, Frederic; Collard, Emmanuel; Alquier, Daniel
Abstract: In this work, non-recessed and Au-free low resistance Ohmic contacts are investigated on AlGaN/GaN on silicon. Based on Ti/Al bilayers, Circular TLM are fabricated and contact values are extracted varying different parameters such as single and combined annealing temperatures and surface treatment. Alloy formation upon annealing has been monitored by XRD. The results indicated that two phases, Ti3 AlN and cubic TiAl3, have been formed upon annealing. Furthermore, the increase of Al thickness (up to 240 nm) resulted in a tetragonal TiAl3 phase formation, with a contact resistance degradation. Finally, we have shown that a low contact resistance (1 Ω mm) is achievable after clean 1 (Caro's + SC1 + HF) and upon annealing at 500 °C for 3 min and 800 °C for 30 s when using 70 nm and 180 nm of Ti and Al, respectively. In this case, the presence of an additional Ti3 AlN (111) phase has been identified and is certainly the origin of the high quality of the Ohmic contact.